Peran Dinas Perpustakaan dan Arsip Daerah Provinsi Jambi dalam Menumbuhkan Minat Baca Masyarakat Melalui Pojok Baca Digital di SAMSAT Kota Jambi - Octaviani, Wenny; Putri, Riska Amalia (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Based on the writing that was done, the following results and conclusions were obtained: The Role of the Jambi Province Library and Archives Service in Growing Public Interest in Reading Through Digital Reading Corners at the Jambi City Samsat, therefore it can be seen that the Role of the Jambi Province Library and Archives Service is: Collaboration with Various Agencies One of which is the Samsat Digital Reading Corner, Increasing Accessibility of Books and Information, Literacy Programs and Socialization. Obstacles Faced by the Jambi Province Library and Archives Service in Growing Public Interest in Reading Through Digital Reading Corners at the Jambi City Samsat, namely: Limited Infrastructure and Technology, Lack of Public Awareness and Interest, Maintenance and Maintenance of Facilities and Efforts to Overcome the obstacles faced by the Jambi Province Library and Archives Service in Growing Public Interest in Reading Through Digital Reading Corners at the Jambi City Samsat, namely: Providing a More Diverse and Interesting Reading Collection Periodic Maintenance and Update of Facilities and Increasing Socialization and Education.